Quality of life among women with postpartum urinary incontinence: A cross-sectional study - Yi Liang; Yiqian Chen; Xiaojie Yu; Xiaodan Li (BMJ Publishing Group, 2021)
Objective: To provide a general description of women with postpartum urinary incontinence (PPUI), and investigate the effect of different types of PPUI with varied severity on affected women's quality of life. Methods: We performed a cross-sectional study in China that included 130 women with reported symptoms of PPUI. At the sixth to eighth week postpartum, we analyzed sociodemographic and clinical characteristics and compared women's quality of life (measured using the I-QOL and IIQ-7) by severity of PPUI (measured using the ICI-Q-SF), types of PPUI, stages of prolapse, and age. Results: 81 of the (62.3%) participating women were classified as mild PPUI, 43 as (33.1%) moderate, and 6 as (4.6%) severe, with 80 of these (61.5%) were grouped into stress urinary incontinence (SUI). With the symptoms of PPUI becoming more severer the total I-QOL score decreased significantly, and the total IIQ-7 score increased. Women with MUI reported lower scores for I-QOL and behavioral impacts, and higher scores of IIQ-7 than those with SUI. Conclusions: We found that more severe symptoms of UI and prolapse more negatively affected the quality of life of postpartum women, and women with MUI experienced a lower QOL.